Arabic Language Learning by Using The Book of Al-Arobiyah Lin-Nasyi'in with a Contextual Approach in Developing Students' Speaking Skill - A’la, Muhamad Rofiul; Aziz, Abdul; Suriani, Erma; Mukadam, Abdur Rasheed Mahmoud (UIN ANTASARI, 2023)
This research included qualitative descriptive approach. The methods used in data collection were observation, interview and documentation methods. The observation method was used to obtain information by observing activities or efforts made by teachers in developing speaking skill (maharoh kalam) without having to be involved in it. The interview method was used to obtain data or information related to how the learning of Al-arobiyah Linnasyi'in book and the Arabic language learning process. While the documentation method was used to obtain data and information related to abu Darda' Islamic Junior High School in Central Lombok. The results of the research conducted by researcher at abu Darda' Islamic Junior High School in Central Lombok were, the teachers had a big role in developing students' speaking skill, such as teachers trained speaking by giving questions answered by students from the results of memorizing vocabularies in the book of al arobiyah lin nasyi'in. With the existence of the book of al-arobiyah lin nasyi'in and the contextual approach conducted by the teachers to develop the students' speaking skill, these efforts made students more confident in improving their abilities in developing their speaking skill, so that teachers used several methods in the learning process, namely direct methods, translation, reading, audiolingual, and mixed method